EXPERIENCES ON AWARDS AND ITS EFFECT - Mehmet TAŞDEMİR and Figen TAŞDEMİR (International Journal of Eurasia Social Sciences, 2016)
This research is a descriptive research. It’s a case study prepared by using qualitative data collection methods. The aim of this research is to raise the applied award-type teacher behaviors which have a positive effect on students at schools and to describe what teachers do about this subject. In the study 4 of the students (%1) indicate that they do not remember any award they gained during their education. 32 of the students (%8) do not express an opinion about the awards they gained and the effect of them. It is seen that 351 of the attendants (%91) have taken awards in 9 different categories. 81(%21) of the awards are verbal congratulation, applause, shown as a good example in a group, 79(%20) of them are stationary materials and food, 69(%18) of them motivating closeness, 46 (%12) of them honor certification, 24(%6) of them graded with high marks, 18(%5) of them the other things, 14(%4) of them given special tasks, 12(%3) students participated in school trips and 8(%8) of them given financial awards.debates on abortion information on abortion nyc abortion clinics